Assessment of the multisectoral approach (MSA) to non-communicable disease (NCD) prevention policies : case studies on tobacco control policies in Togo and in South Africa from 2014 to 2016 - Hongoro, Charles (University of Pretoria, 2018)
Thesis (PhD)--University of Pretoria, 2018.